2019
DOI: 10.1051/0004-6361/201935473
|View full text |Cite
|
Sign up to set email alerts
|

Global 3D radiation-hydrodynamic simulations of gas accretion: Opacity-dependent growth of Saturn-mass planets

Abstract: The full spatial structure and temporal evolution of the accretion flow into the envelopes of growing gas giants in their nascent discs is only accessible in simulations. Such simulations are constrained in their approach of computing the formation of gas giants by dimensionality, resolution, consideration of self-gravity, energy treatment and the adopted opacity law. Our study explores how a number of these parameters affect that measured accretion rate of a Saturn-mass planet. We present a global 3D radiativ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
2
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 68 publications
1
36
2
1
Order By: Relevance
“…We follow here the approaches of our previous works (Bitsch et al 2015b(Bitsch et al , 2019. Even though gas accretion rates are heavily debated in the literature (Ayliffe & Bate 2009;Machida et al 2010;D'Angelo & Bodenheimer 2013;Schulik et al 2019) and span several orders of magnitude in range, we keep these rates as in our previous works to allow a better comparison.…”
Section: Pebble and Gas Accretionmentioning
confidence: 99%
“…We follow here the approaches of our previous works (Bitsch et al 2015b(Bitsch et al , 2019. Even though gas accretion rates are heavily debated in the literature (Ayliffe & Bate 2009;Machida et al 2010;D'Angelo & Bodenheimer 2013;Schulik et al 2019) and span several orders of magnitude in range, we keep these rates as in our previous works to allow a better comparison.…”
Section: Pebble and Gas Accretionmentioning
confidence: 99%
“…However, it seems that 100% efficiency is not realistic in such a case. Schulik et al (2019) showed that gas accretion does not start from the full Hill sphere but only from a fraction of it. The accreted mass fraction increases closer to the planet but it does not accrete 100% of the gas in the vicinity.…”
Section: The Fargo-2d1d Codementioning
confidence: 99%
“…Gas accretion rates onto planets are not very precisely constrained. In the runaway gas-accretion phase accretion, rates Ayliffe & Bate 2009;Machida et al 2010;Schulik et al 2019). Recent studies claim that the accretion rates could be even smaller; Lambrechts et al (2019) found that the mass flux through the envelope is different from the gas accretion rate, therefore, even if the mass flux is on the order of 10 −5 M J yr −1 , the gas accretion rate is actually 10 to 100 times smaller.…”
Section: Influence Of Different Gas Accretion Ratesmentioning
confidence: 99%
See 2 more Smart Citations